Gambaran Kepercayaan Diri Remaja Perempuan Psoriasis di Indonesia - Tika Setiawati; Dian Ariyana (Jurnal Ilmiah Psikologi MIND SET, 2017)
Psoriasis disease can disturb the patient in terms of physical appearance, because the skin changes in the form of thick squama, so that psychologically can affect the quality of life of patients. This study aimed to obtain an overview of the self-confidence of female adolescents with Psoriasis. This study used a qualitative method (case study) with three adolescents women who suffer from Psoriasis since childhood, and used interview as data collection techniques. Results of this study got a description of the self-confidence of female adolescents with Psoriasis to physical appearance to be accepted in the environment. Self-confidence becomes important for female adolescents with Psoriasis to be able to adapt and be accepted by the social environment.